Production of Polypropylene-reinforced Asphalt Concrete Mixtures Based on Dry Procedure and Superpave Gyratory Compactor - Abtahi, Sayyed Mandi; Ebrahimi, Milad Ghorban; Kunt, Mehmet M.; Hejazi, Sayyed Mahdi; Esfandiarpour, Saman (Polymer Research Center Iran, 2011)
Scientists and engineers are constantly trying to improve the performance of asphalt mixtures. Modification of the asphalt binder is one approach used to achieve good mixtures. Fibres and polymers are generally two important modifiers in improving pavement performance, though fibres have received much attention for their enhancement effects among other modifiers for asphalt. In this study, therefore, polypropylene (PP) fibres were selected as fibre modifier because of their low-cost and consistency with asphalt pavement. Asphalt specimens were made by a Superpave gyratory compactor (SGC), analyzed by both Marshall and Superpave methods and tested by Marshall stability apparatus. PP Fibres of two different lengths, i.e., 6 and 12 mm were used at four different percentages of 0.1%, 0.2%, 0.3% and 0.5%, by the total weight of the asphalt concrete. The dry procedure was used to blend fibres with aggregates at the optimized dosage of bitumen, i.e., 4.2%, by weight of the total mix. The experimental results show that adding PP fibre increases the Marshall stability (26%) and the air voids (67%) while reducing the flow (38%) properties. The law of mixtures was used for composite materials to study the fitness of specific gravity of the fibre-reinforced asphalt concrete mixtures with the theoretically calculated values. Thus, it was revealed that the fitness of the real results with the theoretically calculated values is considerable, especially at low percentages of fibres, e.g., 0.1% and 0.2%. It became evident that the existence of voids in all modified and/or neat asphalt-concrete treatments leads samples to completely unfit with the law of mixtures. Finally, the analysis of variance (ANOVA) method and Dennett's test were used to check the accuracy of the results which significantly demonstrates the advantages of using PP fibres in AC mixtures.
Keywords: polypropylene fibres; composite; fibre reinforcement; asphalt concrete; Marshall stability